Glycosides of Nadifloxacin—Synthesis and Antibacterial Activities against Methicillin-Resistant Staphylococcus aureus - Mark Hutchins; Richard A. Bovill; Peter J. Stephens; John A. Brazier; Helen M. I. Osborn (Molecules, 2022)
The increase in the number of bacteria that are resistant to multiple antibiotics poses a serious clinical problem that threatens the health of humans worldwide. Nadifloxacin (1) is a highly potent antibacterial agent with broad-spectrum activity. However, its poor aqueous solubility has limited its use to topical applications. To increase its solubility, it was glycosylated herein to form a range of trans-linked (3a-e) and cis-linked (7a,b) glycosides, each of which was prepared and purified to afford single anomers. The seven glycoside derivatives (3a-e, 7a,b) were examined for potency against eight strains of S. aureus, four of which were methicillin-resistant. Although less potent than free nadifloxacin (1), the α-L-arabinofuransoside (3a) was effective against all strains that were tested (minimum inhibitory concentrations of 1–8 μg/mL compared to 0.1–0.25 μg/mL for nadifloxacin), demonstrating the potential of this glycoside as an antibacterial agent. Estimation of Log P as well as observations made during preparation of these compounds reveal that the solubilities of the glycosides were greatly improved compared with nadifloxacin (1), raising the prospect of its use in oral applications.